Strategi Terpadu Penguatan Industri Makanan Halal di Indonesia: Daya Saing, Keberlanjutan, dan Penetrasi Pasar Global: Integrated Strategy for Strengthening the Halal Food Industry in Indonesia: Competitiveness, Sustainability and Global Market Penetration - Khaerul Aqbar; Azwar, Azwar (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
The halal food industry constitutes one of the strategic sectors with a significant contribution to both the global and national economy. Indonesia’s vast potential, as the country with the world’s largest Muslim population, necessitates well-directed and sustainable strengthening strategies to position the nation as a global hub for the halal industry. This study aims to analyze an integrated strategy for strengthening Indonesia’s halal food industry. The research employs a literature review method, drawing on academic publications, industry reports, and policy documents. The findings reveal four interrelated strategic pillars to enhance the halal food industry in Indonesia: (1) improving productivity and competitiveness, (2) implementing and reinforcing policies and regulations, (3) strengthening finance and infrastructure, and (4) enhancing halal branding and public awareness. Productivity improvements encompass reinforcing the halal value chain, developing competent human resources, empowering business actors including MSMEs and Islamic boarding schools (pesantren), and promoting research and innovation. Policy and regulatory strengthening focus on harmonizing halal standards with international benchmarks and fostering a conducive business climate. Financial and infrastructural support provides a solid foundation for sustainable growth, while strengthening halal branding and awareness shapes market preferences and expands global reach. Consistent implementation of these strategies has the potential to significantly increase the sector’s contribution to GDP, create employment opportunities, and boost exports of halal products.